Fitness costs of increased cataract frequency and cumulative radiation dose in natural mammalian populations from Chernobyl - Lehmann, Philipp (Sci Rep, 2016)
A cataract is a clouding of the lens that reduces light transmission to the retina, and it decreases the visual acuity of the bearer. The prevalence of cataracts in natural populations of mammals, and their potential ecological significance, is poorly known. Cataracts have been reported to arise from high levels of oxidative stress and a major cause of oxidative stress is ionizing radiation. We investigated whether elevated frequencies of cataracts are found in eyes of bank voles Myodes glareolus collected from natural populations in areas with varying levels of background radiation in Chernobyl. We found high frequencies of cataracts in voles collected from different areas in Chernobyl. The frequency of cataracts was positively correlated with age, and in females also with the accumulated radiation dose. Furthermore, the number of offspring in female voles was negatively correlated with cataract severity. The results suggest that cataracts primarily develop as a function of ionizing background radiation, most likely as a plastic response to high levels of oxidative stress. It is therefore possible that the elevated levels of background radiation in Chernobyl affect the ecology and fitness of local mammals both directly through, for instance, reduced fertility and indirectly, through increased cataractogenesis.